Dissemination of Mycobacterium tuberculosis is associated to a SIGLEC1 null variant that limits antigen exchange via trafficking extracellular vesicles. Issue 3 (14th January 2021) - Benet, Susana; Gálvez, Cristina; Drobniewski, Francis; Kontsevaya, Irina; Arias, Lilibeth; Monguió‐Tortajada, Marta; Erkizia, Itziar; Urrea, Victor; Ong, Ruo‐Yan; Luquin, Marina; Dupont, Maeva; Chojnacki, Jakub; et al.
Abstract: The identification of individuals with null alleles enables studying how the loss of gene function affects infection. We previously described a non‐functional variant in SIGLEC1, which encodes the myeloid‐cell receptor Siglec‐1/CD169 implicated in HIV‐1 cell‐to‐cell transmission. Here we report a significant association between the SIGLEC1 null variant and extrapulmonary dissemination of Mycobacterium tuberculosis (Mtb) in two clinical cohorts comprising 6, 256 individuals. Local spread of bacteria within the lung is apparent in Mtb‐infected Siglec‐1 knockout mice which, despite having similar bacterial load, developed more extensive lesions compared to wild type mice. We find that Siglec‐1 is necessary to induce antigen presentation through extracellular vesicle uptake. We postulate that lack of Siglec‐1 delays the onset of protective immunity against Mtb by limiting antigen exchange via extracellular vesicles, allowing for an early local spread of mycobacteria that increases the risk for extrapulmonary dissemination.